Sentimental value and its influence on hedonic adaptation. [article]. - Yang, Yang; Galak, Jeff
Sentimental value is a highly prevalent, yet largely understudied phenomenon. We introduce the construct of sentimental value and investigate how and why sentimental value influences hedonic adaptation. Across 7 studies, we examine the antecedents of sentimental value and demonstrate its effect on hedonic adaptation using both naturally occurring and experimentally manipulated items with sentimental value. We further test the underlying process linking sentimental value and hedonic adaptation by showing that whereas feature-related utility decreases for all items with time, sentimental value typically does not, and that sentimental value moderates the influence of the decrement in feature-related utility on hedonic adaptation. Moreover, this moderating effect of sentimental value is driven by a shift in focus from features of the item to the associations that item possess. We conclude with a discussion of related phenomena and implications for individuals.-- (from the authors)